Albert the great’s refutation against the extramission theory of vision through the extramission theory of reflection - Saparmin, Norzakiah (Kulliyyah of Science, International Islamic University Malaysia., 2019)
Albert the Great (d.1280 CE), i.e., Albertus Magnus was the founder of Christian Aristotelianism, the medieval scholastic venture which reached its culmination in the teachings of his student, Thomas Aquinas (d.1274 CE). His writings reflect his effort in synthesizing Aristotelian philosophy with Christian teachings, and for this paper we would focus on chapter eighth of his work of De sensu et sensato (Sense and Sensibilia), which is entitled “A Digression to Destroy this Error by Considering the Consequences of Their Statements.” The whole treatise of De sensu delineates Albert’s refutation against extramission theory of vision in his task of introducing and establishing Aristotelian intromission theory in the medieval scholastic scholarship. Thus the chapter eighth focuses on Albert’s claim on the absurdities of the extramission theory by refuting on the extramision theory of reflection. We will delineate further what does this theory mean, and the arguments brought forward by Albert against this theory in this particular chapter. Our methodology is a literature review of which we would review also the extramission theory of vision of Plato and Empedocles, the most important proponents of this theory in Greek philosophy, and the intromission theory of Ibn Haytham (d.1040 CE), who was the first scholar to establish scientific evidence of intromission theory. We would later discover that Albert has five major objections against the extramission theory of reflection, and most of his arguments are in the form of reductio ad absurdum, on which he tried to show that all the premises of the extramission theory of reflection, either explicitly derived or implicitly deduced from the theory would only lead to an absurdity or a contradiction of the conclusion. ***************************************************************************** Albert the Great (d.1280 CE), iaitu Albertus Magnus adalah pengasas Kristian Aristotelianisme, pengusaha skolastik abad pertengahan yang mencapai kemuncaknya dalam mengajar muridnya, Thomas Aquinas (d.1274 CE). Karyanya mencerminkan usaha beliau dalam mensintesis falsafah Aristoteles dengan ajaran Kristian, dan untuk penyelidikan ini, penumpuan pada bab kelapan karya De sensu et sensato (Sense dan Sensibilia), yang bertajuk “A Digression to Destroy this Error by Considering the Consequences of Their Statements”. Seluruh risalah De sensumenggambarkan penolakan Albert terhadap teori penglihatan extramissiondalam tugasnya memperkenalkan dan menubuhkan teori intromisi Aristotelian dalam biasiswa skolastik zaman pertengahan. Oleh itu bab kelapan memberi tumpuan kepada tuntutan Albert atas ketidaksuburan teori extramissiondengan menafikan teori reflasi refleksi. Penerangan sejauh mana makna teori ini, dan argumen yang dibawa oleh Albert terhadap teori ini ditrangkan dalam bab ini. Metodologi merupakan kajian kesusasteraan yang akan dibentangkan juga teori penglihatan extramissionPlato dan Empedocles, pendukung paling penting dalam teori ini dalam falsafah Yunani, dan teori intromisi Ibn Haytham (d.1040 CE), yang merupakan sarjana pertama untuk menubuhkan bukti saintifik teori intromisi. Penemuan kajian ini mendapati bahawa Albert mempunyai lima bantahan utama terhadap teori refleksi extramission, dan kebanyakan hujahnya adalah dalam bentuk reductio ad absurdum, di mana beliau cuba untuk menunjukkan bahawa semua premis teori refleksi extramission, sama ada secara diperolehi secara tersurat atau secara tersirat dari teori hanya akan membawa kepada kenyataan yang tidak munasabah atau percanggahan pada kesimpulan.